Dinamika Pertunjukan Lukah Gilo Di Kabupaten Tebo - Apriyulia, Apriyulia; Adriati, ira; Damayanti, Nuning Yanti (LP2M ISBI Bandung, 2025)
Lukah Gilo dance from Tebo Regency, Jambi, originated as a ritual to honour ancestral spirits before planting and harvest seasons. Over time, as socio-cultural dynamics shifted, the dance transformed from a sacred ritual into a secular form of artistic expression performed at public and communal events. This study describes the transformation of Lukah Gilo’s function and meaning in response to social change. The research adopts a qualitative approach using contemporary ethnography by Hammersley & Atkinson, combined with historical methods through the stages of heuristics, verification, interpretation, and historiography. The findings reveal three developmental phases: a ritual-based pre-independence era, an innovation phase in the early 2000s with two stylistic variations (Semabu Village and the Tebo Regency arts team), and an ongoing preservation phase. These changes are shaped by government support, artistic reinterpretation, community participation, and environmental factors. The study underscores how traditional performances can adapt to modern contexts while maintaining cultural identity.